State of the art of UV water treatment technologies and hydraulic design optimisation using computational modelling. (June 2021) - Shah, Jainil; Židonis, Audrius; Aggidis, George
Highlights: Effectiveness of UV in comparison with other water disinfection technologies. Beneficial use of CFD in optimisaton of the Geometrical features of UV technology. Investigating the effect of Geometry on the UV dose received by the water. Exploration of various turbulence and fluence modelling affecting UV technology. Scope and appraisal of using LED lamps in full-scale water treatment plants. Abstract: Water disinfection is an essential process for drinking water use. One of the water treatment process stages includes the application of Ultraviolet (UV) light to assist with the removal of pathogens and viruses such as Cryptosporidium. The previous review in the UV treatment system explores the optical and reaction of microorganisms to the technology. The aim of this paper is to explore the hydraulics and modelling of the current technology of the UV treatment process. There has been enormous progress made in the process of optimisation using Computational Fluid Dynamics (CFD). Due to the expensive nature of the experiments, CFD has emerged as a vital tool. This article explores two essential parts of the UV system that includes the hydraulic system and the modelling. It also explores the effects of design improvements on the UV dosage and overall disinfection efficiency.